Dosimetric comparison of the carotid arteries in patients of T1 and T2 N0 M0 carcinoma glottis by three-dimensional conformal radiotherapy versus carotid sparing intensity-modulated radiotherapy technique - Sathya SB,; Sathiyan K,; Harish Karthick R,; Vijayasree TN, (Asian Journal of Medical Sciences, 2025)
Background: Radiotherapy (RT) is a cornerstone in the treatment of early-stage glottic carcinoma (T1 and T2 N0 M0). However, RT can lead to radiation-induced vasculopathy, which increases the risk of cerebrovascular complications. Carotidsparing intensity-modulated RT (Cs-IMRT) has been proposed to minimize radiation exposure to the carotid arteries while maintaining effective tumor control. Aims and Objectives: This study aimed to compare the dosimetric impact of three-dimensional conformal RT (3DCRT) and Cs-IMRT on carotid artery exposure in patients with T1 and T2 N0 M0 carcinoma of the glottis. Materials and Methods: This prospective comparative study included 30 patients equally divided into 3DCRT and Cs-IMRT treatment arms. Dosimetric parameters, including carotid artery dose exposure (V5Gy, V25Gy, and V50Gy), mean carotid dose, and local control rates, were analyzed. Results: The mean carotid artery dose was lower in the Cs-IMRT group (43.2±9.7 Gy) than in the 3DCRT group (46.9±5.3 Gy, P=0.004). Cs-IMRT demonstrated a significant reduction in high-dose exposure, with V50Gy being 10.2±5.8% for Cs-IMRT versus 42.7±20.1% for 3DCRT (P<0.001). Similarly, Cs-IMRT achieved dose constraints more effectively, with 73.3% of patients meeting the V50Gy=0 criterion compared with none in the 3DCRT group. Although Cs-IMRT showed a slight improvement in local control rates, the difference was not significant (P=0.382). Conclusion: Cs-IMRT showed significant dosimetric advantages over 3DCRT by reducing carotid artery radiation exposure, potentially lowering the risk of radiation-induced carotid artery vasculopathy. While both techniques achieved similar local control, the reduced vascular toxicity associated with Cs-IMRT supports its preferential use in early-stage glottic carcinoma.